2021
DOI: 10.1016/j.jhin.2021.03.004
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 outbreak and healthcare worker behavioural change toward hand hygiene practices

Abstract: Background The coronavirus disease (COVID-19) pandemic has affected healthcare workers (HCW) in their clinical practice. HCW were challenged with new guidelines and practices to protect themselves from occupational risks. We wished to observe if hand hygiene behavior by real-time measurement was related to the dynamic of the epidemic, and the type of patient being cared for in France. Methods This study used an automated hand hygiene recording system to measure HCW hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 23 publications
4
57
0
6
Order By: Relevance
“…Likewise, to ensure employees' and patients' safety, this is also internationally defined for healthcare professionals by the World Health Organisation and Patient Safety [151]. With regard to the COVID-19 pandemic, considering increased hand hygiene, sufficient performance was shown among healthcare workers, nurses and midwives [140,141,152,153].…”
Section: Personal Health-promoting Behaviourmentioning
confidence: 99%
“…Likewise, to ensure employees' and patients' safety, this is also internationally defined for healthcare professionals by the World Health Organisation and Patient Safety [151]. With regard to the COVID-19 pandemic, considering increased hand hygiene, sufficient performance was shown among healthcare workers, nurses and midwives [140,141,152,153].…”
Section: Personal Health-promoting Behaviourmentioning
confidence: 99%
“…The findings are in line with the study by Huang et al . who also used an EHHMS in a French Hospital to register the HHC from September 2019 through to November 2020 and found that the HHC on room entry decreased over time ( 18 ). The authors concluded that the HH behavior of the HCWs was related more to self-protection rather than patient protection.…”
Section: Discussionmentioning
confidence: 99%
“…[11,12]. In France, the HH rate dropped by 9.87% post-lockdown after the first wave of COVID-19; the authors explained that the behavior of HCW was probably altered based on their perceived risk of catching COVID-19 i.e., compliance to HH correlated with the epidemic curve of SARS-CoV-2 [13]. Moore et al also noted a fall in the adherence to HH from 60% to 54% as the pandemic of COVID-19 progressed [14].…”
Section: Discussionmentioning
confidence: 99%